Programmed cell death pathways in cancer: a review of apoptosis, autophagy and programmed necrosis - Ouyang, L. (Cell Prolif, 2012)
Programmed cell death (PCD), referring to apoptosis, autophagy and programmed necrosis, is proposed to be death of a cell in any pathological format, when mediated by an intracellular program. These three forms of PCD may jointly decide the fate of cells of malignant neoplasms; apoptosis and programmed necrosis invariably contribute to cell death, whereas autophagy can play either pro‐survival or pro‐death roles. Recent bulk of accumulating evidence has contributed to a wealth of knowledge facilitating better understanding of cancer initiation and progression with the three distinctive types of cell death. To be able to decipher PCD signalling pathways may aid development of new targeted anti‐cancer therapeutic strategies. Thus in this review, we present a brief outline of apoptosis, autophagy and programmed necrosis pathways and apoptosis‐related microRNA regulation, in cancer. Taken together, understanding PCD and the complex interplay between apoptosis, autophagy and programmed necrosis may ultimately allow scientists and clinicians to harness the three types of PCD for discovery of further novel drug targets, in the future cancer treatment.